Paradigms of Arabic Language Learning: A Critical Review of Religious Linguistics, Interdisciplinary Perspectives, and Arabic for Specific Purposes (ASP) - Widiya Yul; Ahmad Fikri; Riko Andrian (Universitas Islam Negeri Palangka Raya, 2026)
The increasing diversification of Arabic language education in Islamic higher education has generated competing learning paradigms that often operate in isolation and produce fragmented learner competencies. This study critically examines three dominant paradigms of Arabic language learning at the State Islamic Institute of Kerinci: Religious-Linguistics, the Interdisciplinary Approach, and Arabic for Specific Purposes (ASP). Employing a qualitative critical review design, the study analyzes the epistemological foundations, pedagogical orientations, strengths, and limitations of each paradigm within contemporary Arabic language education. The findings reveal that the Religious-Linguistics paradigm effectively develops classical textual literacy and Islamic scholarship but provides limited support for communicative competence in modern contexts. The Interdisciplinary Approach enhances academic relevance across disciplines, yet its engagement with turāth-based literacy remains insufficient. Meanwhile, ASP strengthens professional and academic communication skills but tends to emphasize technical language functions at the expense of broader epistemological and value-oriented dimensions. The analysis demonstrates that the separation of these paradigms contributes to an imbalance in students’ intellectual, communicative, and professional competencies. In response, this study proposes an Integrative Arabic Learning Paradigm that synthesizes epistemological, dialogical, and pragmatic dimensions into a unified framework. This model offers a conceptual foundation for developing more holistic, context-responsive, and globally competitive Arabic language curricula in Islamic higher education.